The combined effects of probiotic CLOSTAT® and Aviboost® supplement on growth performance, intestinal morphology, and immune response of broiler chickens - Ahmed Abed; Ismail Radwan; Ahmed Orabi; Khaled Abdelaziz (German Journal of Veterinary Research)
The present study assessed the effects of dietary supplementation of probiotic CLOSTAT, alone or in combination with Aviboost® supplement, on growth performance, intestinal histomorphology, and immune response in broiler chickens. A total of 600 one-day-old broiler chicks were divided into three groups: G1 (non-treated negative control group), G2 (probiotic CLOSTAT®- and Aviboost®-treated group), and G3 (probiotic CLOSTAT®-treated group). Feed intake and mean body weight were measured weekly for all groups. Sera were collected for cytokine analysis, and duodenal samples were also collected for histomorphological examination. The results revealed that the mean body weight gain was significantly increased to 2.25 and 2.2 kg/bird in G2 and G3, respectively, compared to 1.95 kg/bird in G1. Similarly, the feed conversion ratio (FCR) was improved to 1.56 and 1.59 in G2 and G3, respectively, compared to 1.8 in G1. Serum interferon-γ (IFN-γ) and interleukin (IL)-6 protein concentrations were significantly increased in G2 and G3 compared to G1. Furthermore, the absorptive cells of the villi revealed structural changes, including hyperplasia and increased goblet cell population and microvilli height, in G2 and G3 compared to G1. The lamina propria of duodenal villi in G2 and G3 showed increased cellularity at 22 days of age. In conclusion, concurrent supplementation of CLOSTAT® and Aviboost® to broiler chickens slightly improved the body weight gain and FCR but did not exhibit synergistic or additive effects on intestinal morphology and systemic immune response